STRATEGI OPERASIONAL BISNIS KONSULTAN DI JAKARTA UNTUK MERAIH PELUANG YANG LEBIH BAIK - Aziz Winardi, Muhammad (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract. This thesis aims to analyze the Cause Factors of ability decreased of the Company to obtain of work packages (projects). Methods of data collection are interviews and questionnaires. Tools of strategy used include: Matrix of External Factor Evaluation (EFE), Matrix of Internal Factor Evaluation (IFE), Matrix of Competitive Profile (CP), Matrix of Threats-Opportunities-Weaknesses-Strengths (TOWS), Matrix of Strategic Position and Action Evaluation (SPACE), Matrix of Boston Consulting Group (BCG), Matrix Internal-External (IE), Matrix of Grand Strategy (GS), Matrix of Quantitative Strategic Planning (QSP). The results of the analysis of the Operational Strategy of Business Consultants as follows: Conducting Market Penetration, Development of Consultancy services, Retrenchment and Joint Venture. Keywords: Operational Strategy of Business, Market Penetration, Development of Consultancy Services, Retrenchment, Joint Venture.